PERAN PUBLIC RELATION KING ROSETAIL INDONESIA DALAM MEMBANGUN STRATEGI KOMUNIKASI BISNIS IKAN CUPANG HIAS MELALUI AKUN INSTAGRAM ASTISCUPANG.KRT - Muhammad Arya Jepara (2022)
The business communication strategy process carried out by @artiscupang.krt is motivated by marketing needs that still rely on Instagram social media as the most important communication tool, which has been successful, this can be seen from the process and role of PR in designing ornamental betta fish business strategies and complaints, income The monthly income earned per month is also large and the number of followers of the Instagram account itself, because the majority of Instagram users are young people and are on target to carry out a broader strategy. The communication strategy process carried out by @artiscupang.krt in planning Instagram communication is to use Instagram for monitoring, in this case what has been done is quite optimal and good. And this is where the role of public relations @artiscupang.krt conveys as detailed information as possible to the public and their followers.